Evaluation of serum miR‐216a and miR‐375 as biomarkers in dogs with acute pancreatitis. (3rd December 2022) - Lee, Dohee; Yun, Taesik; Koo, Yoonhoi; Chae, Yeon; Choi, Minseok; Kang, Byeong‐Teck; Yang, Mhan‐Pyo; Kim, Hakhyun
Abstract: Background: Serum microRNAs have emerged as biomarkers of various diseases. Overexpression of serum miR‐216a and miR‐375 occurs in dogs with experimentally induced acute pancreatitis (AP). Objectives: To identify the possibility of using serum miR‐216a and miR‐375 as biomarkers for the diagnosis and evaluation of treatment response in dogs with naturally occurring AP. Animals: Twenty‐one dogs with AP and 20 healthy dogs. Methods: Cross‐sectional study. The relative expression of serum hsa‐miR‐216a‐5p, cfa‐miR‐216a, and cfa‐miR‐375 were analyzed using reverse transcription and real‐time PCR. Results: A significant difference in the serum expression of cfa‐miR‐375 was found between dogs with AP (median [interquartile range] 3.59 [1.55‐24.52]‐fold) and healthy dogs (0.81 [0.54‐2.21]‐fold, P  < .001), and no significant differences were observed in hsa‐miR‐216a‐5p and cfa‐miR‐216a ( P  > .05). The area under the receiver operating characteristic curve of serum cfa‐miR‐375 for differentiating between AP dogs and healthy dogs was 0.84 (95% confidence interval [CI]: 0.71‐0.96). The expressions of hsa‐miR‐216a‐5p and cfa‐miR‐375 were positively correlated with the concentrations of serum C‐reactive protein ( r s  = .46, r s  = .48, respectively), but not with the serum specific canine pancreatic lipase. The expression of cfa‐miR‐375 was significantly less after treatment in dogs with AP ( P  = .02). Conclusions and Clinical Importance: Serum cfa‐miR‐375 could be a potential biomarker for the diagnosis and evaluation of treatment response of AP in dogs. In addition, miR‐216a and miR‐375 could be associated with inflammatory processes in dogs with AP.